How Ficta Follow Fiction A Syncretistic Account of Fictional Entities - Voltolini, Alberto; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book presents a novel theory of fictional entities which is syncretistic insofar as it integrates the work of previous authors. It puts forward a new metaphysical conception of the nature of these entities, according to which a fictional entity is a compound entity built up from both a make-believe theoretical element and a set theoretical element. The fictional entity is constructed by imagining the existence of an individual with certain properties and adding a set-theoretical element consisting of the set of properties corresponding to the properties of the imagined entity. Moreover, the book advances a new combined semantic and ontological defence of the existence of fictional entities.
The Metaphysical Side -- The Committal Theories (I) -- The Committal Theories (II) -- The Syncretistic Theory -- Further Developments of the Syncretistic Theory -- The Semantic Side -- The Noncommittal Theories -- The Syncretistic Theory -- The Ontological Side -- An Ontological Argument in Favor of the Existence of Fictional Entities.
Keywords: PHILOSOPHY (GENERAL).; METAPHYSICS; ONTOLOGY; LINGUISTICS -- PHILOSOPHY; PHILOSOPHY; METAPHYSICS; PHILOSOPHY OF LANGUAGE; ONTOLOGY